2015
DOI: 10.3174/ajnr.a4252
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Axonal Metabolism during Early Natalizumab Treatment in Relapsing-Remitting Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:The considerable clinical effect of natalizumab in patients with relapsing-remitting multiple sclerosis might be explained by its possible beneficial effect on axonal functioning. In this longitudinal study, the effect of natalizumab on absolute concentrations of total N-acetylaspartate, a marker for neuronal integrity, and other brain metabolites is investigated in patients with relapsing-remitting multiple sclerosis by using MR spectroscopic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…While this was the only statistically significant metabolite change, there was also a statistical trend for NAA increase in moderately hypointense lesions. With this caveat, we note that findings of increasing NAA in lesions and NAWM can be attributed to medication [Khan et al, ; Narayanan et al, ; Wiebenga et al, ], and therefore it can be speculated that our results suggest such an effect, but only in moderately hypointense lesions.…”
Section: Discussionsupporting
confidence: 86%
“…While this was the only statistically significant metabolite change, there was also a statistical trend for NAA increase in moderately hypointense lesions. With this caveat, we note that findings of increasing NAA in lesions and NAWM can be attributed to medication [Khan et al, ; Narayanan et al, ; Wiebenga et al, ], and therefore it can be speculated that our results suggest such an effect, but only in moderately hypointense lesions.…”
Section: Discussionsupporting
confidence: 86%
“…Whether the observed stabilization of GM damage is due to a neuroprotective effect of natalizumab deserves further investigation in appropriately designed studies. Some studies have already pointed to this hypothesis using MRI 32,33 , with recent studies using spectroscopy showing that natalizumab increases the levels of N-acetylaspartate, creatine and phosphocreatine, maybe indicating an enhanced axonal metabolism in natalizumabtreated patients 34 and reduction of WM damage during the first year of treatment using diffusion tensor imaging 35 . Finally, body fluid biomarkers in a progressive MS study with patients treated with natalizumab also showed a reduction in intrathecal inflammation (decreased levels of osteopontin) accompanied by decreases in other markers of neurodegeneration (neurofilament light chain) and tissue damage (increases in MTR in cortical GM and normal-appearing WM) 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the clinical benefits of natalizumab therapy seen in phase III studies of patients with relapsing forms of MS [Polman et al 2006;Rudick et al 2006], other studies have revealed evidence of enhanced tissue integrity and improved axonal metabolism in some natalizumab-treated RRMS patients, suggesting that reducing inflammation may enable endogenous repair mechanisms to take place during natalizumab therapy [Fox et al 2011;Wiebenga et al 2015]. While it is unclear whether or to what extent this may be pertinent in SPMS, it is encouraging that natalizumab treatment improved magnetization transfer ratios in the cerebral cortex and normal-appearing white matter of SPMS/ PPMS patients [Romme Christensen et al 2014].…”
Section: Discussionmentioning
confidence: 99%